Data and reports for project 'Under stilleben: Material analysis of a portrait miniature at Nationalmuseum', RAÄ-2022-2572 - Canosa, Elyse; Daudin Schotte, Maude; Sandström, Tom; Hinrichs Degerblad, Kathrin (Swedish National Heritage Board, 2024)
Data from the project 'Under stilleben: Material analysis of a portrait miniature at Nationalmuseum' (Diarienummer RAÄ-2022-2572). Data from the following analytical techniques is included: 1. Fourier transform infrared spectroscopy (FTIR); 2. Raman spectroscopy; 3. Reflectance transformation imaging (RTI). Also included are instrument reports which compile the data, provide the measurement parameters and describe the samples/measurement areas for each technique. The intention of the project was to aid in conservation treatment decisions of a portrait miniature in Nationalmuseum's collection (Blomsterstilleben by Anne Vallayer-Coster, inventory number NMB 2667, https://collection.nationalmuseum.se/sv/collection/item/174329/) by using FTIR to identify the adhesive used to adhere the canvas painting to a glass cover, Raman spectrscopy to identify the presence of formate glass deterioration products, and RTI to observe the topography of the painting under the glass cover.
Keywords: Heritage Science; RAÄ-2022-2572; Nationalmuseum; Portrait miniatures; Fixé sous verre; Anne Vallayer-Coster; FTIR; Raman spectroscopy; Reflectance transformation imaging; Glass corrosion; History and Archaeology; Historia och arkeologi